Renewable H-2 from glycerol steam reforming: effect of La2O3 and CeO2 addition to Pt/Al2O3 catalysts. - Montini, Tiziano; Singh, Rakesh; Das, Piyali; Lorenzut, Barbara; Bertero, Nicolas; Riello, Pietro; Benedetti, Alvise; Giambastiani, Giuliano; Bianchini, Claudio; Zinoviev, Sergey; Miertus, Stanislav; Fornasiero, Paolo (Chemsuschem, 2010)
Glycerol is the main byproduct of biodiesel production and its increased production volume derives from the increasing demand for biofuels. The conversion of glycerol to hydrogen-rich mixtures presents an attractive route towards sustainable biodiesel production. Here we explored the use of Pt/Al2O3-based catalysts for the catalytic steam reforming of glycerol, evidencing the influence of La2O3 and CeO2 doping on the catalyst activity and selectivity. The addition of the latter metal oxides to a Pt/Al2O3 catalyst is found to significantly improve the glycerol steam reforming, with high H-2 and CO2 selectivities. A good catalytic stability is achieved for the Pt/La2O3/Al2O3 system working at 350 degrees C, while the Pt/CeO2/Al2O3 catalyst sharply deactivates after 20 h under similar conditions. Studies carried out on fresh and exhausted catalysts reveal that both systems maintain high surface areas and high Pt dispersions. Therefore, the observed catalyst deactivation can be attributed to coke deposition on the active sites throughout the catalytic process and only marginally to Pt nanoparticle sintering. This work suggests that an appropriate support composition is mandatory for preparing high-performance Pt-based catalysts for the sustainable conversion of glycerol into syngas.
Keywords: biofuels; Glycerol; heterogeneous catalysis; platinum; supported catalysts

Towards biodegradable elastomers: green synthesis of carbohydrate functionalized styrene-butadiene-styrene copolymer by click chemistry - Singh, Rakesh; Varma, Anjanikumar (Green Chemistry, 2012)
Random attachment of sugar molecules to synthetic polymers is an important strategy to induce biodegradability in these polymers. The present study successfully employs ``click'' chemistry to introduce low levels of sugar molecules onto styrene-butadiene-styrene (SBS) copolymer, a widely used commodity polymer which is not biodegradable. Spectral, morphological and thermal studies of the modified polymers were carried out to show the dramatic changes in the properties of these modified polymers. Thermal stability of glucose linked SBS had onset of degradation at 428 degrees C, down from 478 degrees C observed for SBS. Morphology studied by WAXRD and SEM showed destructuring of the polymer domains of SBS, which is beneficial for biodegradation of these polymers. Previous studies showed that sugars anchored by hydrolysable ester groups onto polystyrene were biodegradable; current studies show that sugars anchored by unhydrolyzable C-C bonds on the butadiene component of SBS copolymer are also significantly biodegradable.